Effects of malonic acid crosslinked starch for soil strength improvement - Im, Jooyoung; Chang, Ilhan; Cho, Gye Chun (Transportation Geotechnics, 2021)
The strengthening behavior of crosslinked starch using malonic acid is examined in this study. Since the conventional binding materials used in construction engineering practices have been shown to be environmentally hazardous, the use of eco-friendly and biological approaches (e.g. microbial induced calcite precipitation, biopolymer-based soil treatment) has been studied in recent years. Among such methods, biopolymers have a large variety of possible applications in the field of construction engineering. Biopolymers can enhance soil strength, reduce soil hydraulic conductivity, improve erosion resistance, and even promote vegetation growth. However, most of the biopolymers studied have shown several limitations and challenges for their reliable use. The use of crosslinking may help alter specific properties of biopolymers for soil enhancement. In this study, the strengthening behavior of crosslinked starch using malonic acid was examined. Various parameters for the crosslinking effect were measured and their effect on the soil strength was observed. Results showed that the binding strength of starch could be enhanced for soil strengthening with the use of crosslinking but was highly sensitive to the duration of the applied heat.
Keywords: Biopolymer; Crosslinking; Heat; Hydrolysis; Malonic acid; Starch; Strength; Time; Unconfined compressive strength (UCS)